Perbandingan Pemanfaatan Industri Migas oleh Perusahaan Minyak dan Gas Nasional Petrobras dan Sinopec - Zalwa Apriliana Sesa; Baginda Goldy Hamonangan; Najla Ramadhanthi Yuristiannisa; Saphira Anindhita Putri Pratama (Universitas Islam Darul Ulum Lamongan, 2021)
National oil and gas companies are an important sector in the national development of a country, both in terms of meeting the needs of energy and industrial raw materials in the country so that their management must be carried out optimally. This study was conducted to determine the comparison of the national oil and gas company owned by Brazil, namely Petrobras and owned by China, namely Sinopec in conducting exploration of the oil and gas industry. The research method used in writing this article is descriptive qualitative. This method aims to describe in general the differences between national oil and gas companies owned by Brazil and China and then focus on certain phases to be able to find some specific aspects intensively and in depth. The data collection technique used is library research from various literatures that are relevant to the subject matter of the research object, in the form of books, journals, and articles from the internet. The data analysis technique used is qualitative with a case study approach. Relevant data were collected and then analyzed qualitatively, namely by connecting one phenomenon to another to draw a final conclusion on the conditions of comparable differences between the two national oil and gas companies from these two different countries in exploiting and exploring natural resources and ensuring their availability. Even though both are present as national oil and gas companies, Petrobras and Sinopec have their own strategies and methods in utilizing the oil and gas industry.